2014
DOI: 10.1088/0004-637x/790/2/96
|View full text |Cite
|
Sign up to set email alerts
|

On the Validity of Collider-Mass Scaling for Molecular Rotational Excitation

Abstract: Rate coefficients for collisional processes such as rotational and vibrational excitation are essential inputs in many astrophysical models. When rate coefficients are unknown, they are often estimated using known values from other systems. The most common example is to use He-collider rate coefficients to estimate values for other colliders, typically H 2 , using scaling arguments based on the reduced mass of the collision system. This procedure is often justified by the assumption that the inelastic cross se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Walker et al (2014) demonstrated on both theoretical and numerical grounds that this standard reduced-mass scaling approach is typically invalid. We therfore do not recommend here that such an approach be adopted with the present HF-He rate coefficients.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Walker et al (2014) demonstrated on both theoretical and numerical grounds that this standard reduced-mass scaling approach is typically invalid. We therfore do not recommend here that such an approach be adopted with the present HF-He rate coefficients.…”
Section: Applicationsmentioning
confidence: 99%
“…Given the availability of HF-H 2 and HF-He collisional data, we can test various scaling methods, including the reduced-potential approach introduced in Walker et al (2014). In the reducedpotential method, the collisional data are scaled by the reduced potentials µ X ε X according to…”
Section: Prediction Of Hf Rate Coefficients By Scalingmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, high-resolution observations of star-forming regions and protoplanetary disks of young stellar objects have shown evidence of rovibrational transitions for states where rate coefficients are currently lacking. In order to model such environments, current simulations have relied on approximate scaling methods which are known to be unreliable 17,18 .…”
Section: Introductionmentioning
confidence: 99%